ANALISIS BISNIS KAPAL KARGO CURAH DENGAN VALUE CHAIN ANALYSIS STUDI KASUS: PELABUHAN TANJUNG INTAN CILACAP - Danis Maulana (INOVTEK POLBENG, 2020)
Every operated ship has at least two auxiliary engines that are used to supply electrical energy needs such as for air conditioners, lights, navigation equipment, ship cranes, and so on. To activate the auxiliary engine, fuel is needed. In fact, fuel oil for ships weighs 54% of the operating costs component that the shipping company must be incurred. Therefore, the company needs more economical electricity supply, so that it can reduce and optimize its operational costs which can lead to profits enhancement. This study aims to determine the comparison of the most economical use of electricity supply between auxiliary engines and the shore connections when ships carry out loading and unloading activities at Tanjung Intan Port, Cilacap. The method used in this study is the calculation approach of ship's electricity and business. The business analysis uses the value chain analysis method. The object of this research is the 26.562GT bulk carrier ship which was carrying out loading and unloading activities at the Port of Tanjung Intan Cilacap. From this study’s result, it was found that electricity consumption on PS ships for 6 days of loading and unloading were 12,117 kWh at peak load times (WBP) and 45,256 kWh at over peak load times (LWBP). The use of a shore connection is an economical choice, because the use transfer from using AEs to a shore connection has increased the company's net profit by 17% or as much as Rp1.787.060.325